Cast3M implementation of the extended finite element method for cohesive crack - Giang, Nguyen Truong; Nhu, Ngo Huong (Vietnam Journal of Mechanics, 2011)
In this paper, the finite element for cohesive crack for quasi-brittle materials is constructed by the displacement discontinuities in the element. The algorithm of construction and procedures for involving this finite element into code Cast3M are presented. The numerical calculations in fracture mechanics are presented to demonstrate the benefits of the proposed implementation.